Examining the Factors Contributing to Fintech Peer-to-peer Lending Adoption - Rudy Sunardi; Usep Suhud; Dedi Purwana; Hamidah Hamidah (Journal of Information Systems Engineering and Business Intelligence, 2021)
Background: Peer-to-peer (P2P) lending platform is one of key disruptive business models in financial technology. It bridges lenders and borrowers directly. Researchers have studied the leverage mechanism behind the P2P lending platform.Objective: This research proposes an enhanced technology acceptance model (TAM) to investigate how consumers embrace P2P lending platforms using quality of service and perceived risk as drivers of trust.Methods: This research uses structural equation modeling (SEM) to test the hypothesised connections between the latent variables.Results: The findings show that users' trust, perceived usefulness, and perceived ease of use in P2P lending platforms significantly influence attitudes towards adoption. Meanwhile, consumers' perceived risk in using P2P lending platforms is unaffected by the quality of service.Conclusion: The estimated model is consistent with the results shown in previous studies.  The findings of the current research are useful for fine-tuning platform marketing plans and putting strategic goals into actions. For future research, we suggest including more variables to better understand the adoption intention of P2P lending platforms.Keywords: Adoption intention, Peer-to-peer lending, Structural equation modeling, Technology acceptance model